EFFECT OF DRINKING IONIZED WATER ON HISTOLOGICAL CHANGES, BACTERIA COUNT, AND SOME HEMATOLOGICAL PARAMETERS OF JAPANESE QUAIL - Hasanain N. Ezzat; Mohammed A. Hussein; I. M. Shihab; M. F. A.Al-Qazzaz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was conducted to study the effect of drinking ionized water on histological changes, bacteria count, and some hematological parameters of Japanese quail. A total of 200-42-day-old female Japanese quails were divided into five treatments four replicates each treatment (40 birds/replicate). The birds of each treatment were divided into four replicates. The pH level of drinking water of the first treatment was 7, whereas the pH levels of drinking water of other treatments were 8, 9, 6, and 5 respectively. The results showed that villi height, crypt depth, and mucous layer thickness of the duodenum were increased (P<0.05) in T4 and T5. The normal histological structure was observed in the microscopic section of the liver of the treated group. Also, the pH9 of drinking water showed large vacuoles in the epithelial layer which support the lymphoid follicles in the section of the bursa. There were thickening and degeneration changes in the capsule with lymphocyte aggregation in birds that received pH9 of drinking water. The levels of pH of drinking water affect WBC, Hb, and PCV. Drinking acidic ionized water increased the number of Lactobacilli bacteria and decreased the number of Coliform bacteria.